Pengembangan Need Assesment Pada Penentu Kebijakan Dan Stakeholder Dalam Program Kawasan Tanpa Rokok (KTR) Di Kantor Kecamatan Dukun Kabupaten Magelang - Punik Mumpuni Wijayanti; Arif Rahmat Kurnia; Edi Soeharso (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: A smoking habit mostly has spread to almost groups of societies in Indonesia. This habit tends to increase among children and adolescents. Rights to access fresh air free from smoking have been widely discussed at various world meetings. Therefore, it is necessary to have an in-depth study to increase non-smoking areas in public areas.Objective: This study is to develop a need assessment on policy makers and related stakeholders applying a non-smoking area program (in Indonesia it is called KTR/Kawasan Tanpa Rokok) at District Office of Dukun, Magelang Regency, Central Java.Methods: This study was an observational study with a qualitative approach. Its respondents were determined purposively focusing on the Head of Dukun District, some officials of the District, and its visitors.Results: This study found that a majority of respondents understood effects and impacts of smoking to their health. They requested an issuance of official letter for a non-smoking area. The Head of the District has issued a smoking ban for its officials and employees. This issuance was important to increase comfort of its visitors, employees, and officials. In addition, it could make the Head easier to develop derivative regulations.Conclusion: A defined regulation is necessary to apply the non-smoking area program. A regulation from the Regent is highly suggested, but decisions from related agencies can be considered sufficient. The government and related stakeholders should immediately make a local regulation so that the program can be widely applied in the Dukun District.